Regeneration of Protium pallidum Cuatrec. in clearings originated from selective logging in the Eastern Brazilian Amazon (Research, Society and Development, 2021)
The objective of this research was to evaluate the dynamics of Protium pallidum Cuatrec. Regenerants, in clearings resulting from selective logging, nine clearings were used in this study, ranging in size from 231m2 to 748m2. Each clearing had its center determined and from the edge four strips of 10m x 50m were marked in the North, South, East and West directions. For the evaluation of natural regeneration, three plots of 2m x 2m were implanted in each strip, at distances of 0, 20 and 40m respectively. the mathematical models called Natural Regeneration Rate (TR%), Ingresso (I%) and Mortality (M%) were used. Three-way analysis of variance was performed. There was no significant difference in the TR% values as a function of distances, as well as directions and also as a function of years, however this TR% had the highest values recorded for the South direction and in the plot 40m away in the interior of the sub- grove.